Assessing the severity of injury using the revised trauma score in a tertiary institution in North-Central Nigeria - Gwaram, Usman; Ihezue, Chikwe; Onche, Icha (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background: Current trauma management advocates inclusion of a measure of severity of the injury during evaluation.Aims: To evaluate the validity of the Revised Trauma Score (RTS) in assessment of trauma patients in accident and emergency unit of a tertiary hospital in Nigeria.Materials and Methods: Two hundred and fifty-two consecutive patients 18 years and above with injuries were recruited for the study. Written informed consent was obtained from each of the patients or their relations if unconscious. Each patient was registered according to the guidelines of International Categorization of External Causes of Injuries. The severity of injury was calculated using the RTS and the patients were followed-up, and their condition at discharge was documented.Results: Two hundred and fifty-two patients above the age of 18 years were studied. Mean age of patients' was 32.9 years with the oldest being 72 years. There were 192 male and 60 female with a male to female ratio of 3.2:1. Most of the injuries were following road traffic accidents. Among the patients with minor injuries from the RTS, 71% made full recovery, 25% were handicapped, and 4% died, while 22% of the patients with severe injuries made full recovery, 11% were handicapped, and 67% died.Conclusion: There was a statistically significant relationship between the RTS and outcome (P< 0.05) from the study, and the RTS could be used as a standard physiological trauma scoring system in prediction of outcome in our trauma population.
Keywords: Injury severity; injury outcome; revised trauma score; RTA